Study Perkembangan Rumah Sakit Di Jambi Masa Kolonial Belanda (1906-1942) Sebagai Bahan Ajar Pada Pembelajaran Sejarah Di SMA Negeri 2 Kota Jambi - Sijabat, Nora Cahaya; Reka Seprina (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
Tulisan ini membahas tentang perkembangan Rumah Sakit Jambi masa Kolonial Belanda sebagai pengembangan bahan ajar dalam pembelajaran sejarah. Penelitian ini bertujuan untuk mengidentifikasikan kelayakan materi perkembangan Rumah Sakit Jambi sebagai materi pembelajaran sejarah Indonesia dan untuk peminatan sejarah bagi siswa SMA. Metode yang digunakan dalam penulisan peneIitian ini menggunakan metode penelitian kualitatif yang menggunakan pendekatan peneIitian deskriptif. Sumber yang digunakan dalam penuIisan peneIitian ini adalah sumber kepustakaan yang menggunakan teknik anaIisis sejarah yang menggunakan interpretasi fakta sejarah yang meIiputi buku, dokumen, jurnaI dan observasi terkait This paper discusses the development of Jambi Hospital during the Dutch Colonial period as the development of teaching materials in history learning. This study aims to identify the feasibility of Jambi Hospital development materials as learning materials for Indonesian history and for specialization in history for high school students. The method used in writing this research uses a qualitative research method that uses a descriptive research approach. The sources used in writing this research are literary sources that use historical analysis techniques that use interpretations of historical facts which include books, documents, journals and observations related to the Dutch government health system. The results of this study indicate that the Dutch heritage Jambi Hospital can be used as a source of learning history in Indonesian History and Specialized History subjects. Jambi Hospital has an important role for students because by utilizing the Hospital as a historical source it can also increase feelings of love for the motherland and nationalism towards the nation and they will become more familiar with the history in the surrounding environment and can preserve it for the future